PENGARUH KEPRIBADIAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP SEMANGAT KERJA KARYAWAN FAKULTAS HUKUM UNIVERSITAS MUHAMMADIYAH PALEMBANG - Echi Kurniati (Universitas Sarjanawiyata Tamansiswa, 2025)
The variables selected for this research are personality, work environment, and compensation concerning employees' motivation.The research was conducted at the Faculty of Law, Universitas Muhammadiyah Palembang, located at Jendral Ahmad Yani Street No. 13, Ulu Palembang. The subjects of this research are employees working at the Faculty of Law, Universitas Muhammadiyah Palembang. The population in this study consists of 32 employees working at the Faculty of Law, Universitas Muhammadiyah Palembang. The research method employed is quantitative research. The results of hypothesis testing simultaneously show the influence of the personality variable (X1), work environment (X2), and compensation (X3) on employee motivation (Y). This is based on the F-test result, where the F-value obtained is 331.246 with a significance level of 0.001, while the F-table value is 3.34 with a significance level of 0.05. Consequently, so the null hypothesis is rejected and the alternative hypothesis is accepted. Thus, personality variable (X1), work environment (X2), and compensation (X3) simultaneously have an impact on employee motivation (Y). The Adjusted R-square coefficient obtained is 0.970 (97.0%), indicating that the personality variable (X1), work environment (X2), and compensation (X3) collectively influence employee motivation (Y) by 97.0%, while the remaining 3.0% (100% - 97.0%) can be explained by other unexamined variables in this research. The personality variable (X1) does not significantly affect employee motivation (Y), whereas the work environment (X2) and compensation (X3) significantly influence employee motivation (Y).